Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar dalam Mata Pelajaran Matematika Pada Siswa Kelas IV - Dewi Sinta Rahmawati; Nafia Wafiqni (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
This study aims to determine the increase in learning outcomes of mathematics, the subject of estimation and rounding in IV grade students of SDN in the 2021/2022 academic year. The method used in this research is Classroom Action Research (CAR) which consists of two cycles and four stages. The data collection technique used was observation while students were participating in the learning process and using tests in the form of questions carried out at the end of the cycle as well as documentation during learning activities.The results of this study indicate that there is an increase in students' mathematics learning outcomes using the Project Based Learning (PjBL) learning model in each cycle. In the first cycle, student learning outcomes reached 53% of 32 students and only 17 students completed. Furthermore, in cycle II there was an increase with learning outcomes reaching 91% completeness and only 3 students who did not complete. The conclusion of this study is that efforts to use the Project Based Learning model can improve mathematics learning outcomes for IV grade students at SDN .